Pertumbuhan dan Performansi Warna Ikan Mas Koki (Carassius sp.) Melalui Pengayaan Pakan dengan Kepala Udang - Narti Fitriana; I Wayan Subamia; Seno Wahyudi (Al-Kauniyah: Jurnal Biologi, 2013)
Carotenoids is a pigment that causes yellow, orange and red color. Shrimp head meal was known contain carotenoids that could improve the performance of fish color. The aim of this study is to investigate the effect of enrichment fish food by shrimp head meal to the performance of color and growth at various concentrations in goldfish varieties tossa. Concentrationn of shrimp head meal in feed treatment are 0%, 5%, 10% and 15 %. The results showed difference in performance of goldfish tossa color and growth. Highest growth rate experienced by the fish that were subjected to 0% of shrimp head meal with the value length 11,61 mm and weight 12,76 gram. Value of color performance at the highest end based on measurements using the Toca Color Finder (TCF)  showed by 10% fishtreated with the value of color back 5,31, bellycolor 4,81 ang tailcolor 4,76.